Smart Greenhouse Monitoring With Soil Temperature and Humidity Control on Internet of Things (IoT) Based Orchid Plants - Feri Aditya Ridwan Mas; Sri Wahyu Suciyati; Gurum Ahmad Pauzi; Junaidi Junaidi (Journal of Energy, Material, and Instrumentation Technology, 2022)
Research on monitoring systems with control has been developed with several different inputs and outputs. This research has realized a smart greenhouse monitoring tool with temperature and soil moisture control on orchid plants based on the Internet of Things (IoT). This study aims to create a monitoring tool for temperature, air humidity, soil moisture, and water level. In the system, the microcontroller used is Wemos D1 R1, with inputs in the form of a DHT-11 sensor to measure air temperature and humidity, a soil moisture sensor to measure soil moisture, and an ultrasonic sensor to measure the water level in the containers. The resulting system output is in the form of pump and fan control. Based on the results of sensor testing, the accuracy of the DHT-11 sensor is 99.97%, the error is 0.03%, the soil moisture sensor is 98.63% accurate, the error is 1.37%, and the ultrasonic sensor is 97, 61% with an error of 2.89%. Based on the research results, the system can run well, as shown by Thingspeak, and the website smartgreenhouseanggrek.weebly.com can receive the results of monitoring sensor data using an internet connection. The tool will carry out the process of wateringplants when the soil moisture value read by the sensor is 20% and will stop watering when the sensor reads the soil moisture value reaches >= 50%. In contrast, the air temperature control is done by turning on the fan if the temperature reaches 30° C.